Characterization methods and experimental study of mining-induced rock mass damage and fracture using carbon fiber similar materials - Weibing ZHU; Bozhi ZHAO; Shan NING; Jiahao XIANG (Meitan kexue jishu)
Simulation experiments are a crucial method for investigating overburden failure, strata movement, and strata control during coal mining. However, traditional similar materials struggle to effectively monitor the internal damage, fracturing, and dynamic development processes within the strata during mining. To address this issue, carbon fibers were introduced into the field of similar material simulation experiments for mining. Leveraging the sensitive feedback of resistivity changes in response to damage of this composite material, This enabled real-time monitoring of internal damage and fracture patterns within the mining strata during similar simulation experiments, leading to the development of a carbon fiber similar simulation composite material with damage self-sensing properties. The study found that as the carbon fiber content increased, the evolution patterns of the electrical resistance change rate and the damage coefficient of the similar material tended to coincide. When the carbon fiber content in the similar material exceeded 2%, the electrical resistance change rate and the damage coefficient consistently exhibited synchronized growth with essentially identical increments. Based on this, the correlation between the variation of resistivity in carbon fiber similar simulation materials and the degree of rock layer damage was investigated. Dynamic evolution experiments of the rock structure in close proximity to coal pillar extraction were conducted, focusing on the physical simulation of the timing of key layer fractures. The characteristics of resistivity changes in carbon fiber similar materials throughout the coal mining process were analyzed, enabling precise identification of the development extent, distribution range, and fracture timing of the overburden mining-induced cracks. This research established a novel quantitative and characterization method for the dynamic process of rock layer damage and fracturing applicable in mining engineering simulation experiments. It provides a scientific basis for revealing the evolution of damage and fracture in mining-induced strata and for optimizing rock layer control technologies.